Teacher Leadership. The pathway to Common Core Success - Amore, rew; Hoeflich, Nichole M.; Tuesday, Kaitlin Pennington | (Center for American Progress, 2015)
A new CAP report highlights six districts that are using teacher leadership and labor-management collaboration to successfully implement the Common Core State Standards.